Transposição do rio São Francisco e renda fundiária: uma análise da propriedade camponesa do Alto Paraíba-PB - Melo, Maria José de (2019)
The object of this dissertation is the transposition of São Francisco River, in its east-axis channel, which has the potential to bring water to Paraíba’s Semiarid region. However, the priority of this water usage is the urban supply of Campina Grande city, located in the state of Paraíba. The transposition was partially completed and inaugurated in 2017. The aim of this dissertation is to investigate the economic and social impacts for the peasants that live in the banks of Alto Paraíba/PB, in Paraíba’s microregion Cariri. And the problematic is: since the bed of Paraiba’s River is used in the transposition, the transposition increases the economic fertility of the lands of these banks. To which social classes will this increased fertility belong? The hypothesis is that the transposition waters in Alto Paraíba are reserved for the grand capital’s irrigated production. In order to make this production viable, the grand capital will seek to expropriate the land of peasants located on these banks. The method used in this research work was historical-dialectical materialism: the economic structure of society and the real basis upon which the legal and political superstructure arises (Marx, 1983). The methodology and research instruments used in the dissertation were: 1) the bibliographical study: immanent reading of the Karl Marx’s Book III of The Capital (2008); 2) documentary research: analysis of the transposition project; analysis of documents from federal and state agencies (ANA) and (AESA); analysis of land data from SNCR / INCRA (2017) and the Census of Agriculture / IBGE (2017) on the landholdings of Alto Paraíba; 3) field research: semi-structured interviews with representatives of government agencies and with riverine peasants. The categories of analysis were: Capitalist Land Income, Differential Income II, Virtual Income, Contradiction between tenants and landowners, and Peasant Property. The dissertation is divided into five sections. The state capital of the transposition provides type II differential land income through the access of a natural force, the water, which is a state monopoly. The state provides greater fertility through a natural resource that belongs to the own state, and it would economically have to earn absolute income. Therefore, in this sense, the transposition constitutes a concrete hope, with the arrival of the waters of the São Francisco and, similarly, may pose a threat to the permanence of this small peasant rural property on the banks of the Alto Paraíba, due to its legal condition (possession and / or legal), but mainly due to its “non-capitalist” economic condition, which does not force the grand capital to pay rent to a small landowner, which is why the role of big constructions in the Brazil’s history of agrarian property is the story of the continued expropriation of small peasant property and land concentration in large estates.